Shackled by shame: Men’s reluctance to seek social work help for intimate partner violence victimization - Saunders, Yolanda, U.; Kasa, Luvo (Edelweiss Applied Science and Technology, 2025)
Intimate partner violence cuts both ways, but men as victims in South Africa remain buried under shame and silence. Raised in a world where manhood means toughness, they face punches, insults, and worse from partners—yet they will not talk, let alone reach for social work help. This paper peels back that struggle: why they hide, how patriarchy traps them, and what keeps social workers from breaking through. Pulling from global studies and South African scraps of data, it shows a mix of stigma, cultural chokeholds, and systems blind to their pain. Men’s victimization gets drowned out by the focus on women, leaving them shackled. Men remain ashamed to admit victimization and scared to seek help. This calls for social work to rethink its approach: culturally sharp tools, quiet outreach, and a hard look at what we are missing as social workers. The silence is loud; it is time we listened. Purpose: This is a desktop study that examines why South African men victimized by intimate partner violence (IPV) resist social work help, trapped by shame and cultural norms.